2009
DOI: 10.1007/s00421-009-1149-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term glucocorticoid intake improves exercise endurance in healthy recreationally trained women

Abstract: The present study investigated whether short-term oral administration of glucocorticoid would modify performance and selected hormonal and metabolic parameters during submaximal exercise in healthy women. Nine recreational female athletes completed cycling trials at 70-75% VO(2) max until exhaustion after either placebo (Pla, gelatin) or oral prednisone (Cor, Cortancyl, 50 mg per day for 1 week) treatment, according to a double-blind and randomized protocol. Blood samples were collected at rest; after 10, 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 26 publications
1
33
1
2
Order By: Relevance
“…Although the statistical comparison was made between baseline measurement and post-treatment, and not additionally to the placebo measurements, it seems likely that this is a true effect as there was no change in the placebo treatment. Another study confirmed these findings in untrained females treated with 50 mg prednisone daily for 1 week, which showed a 39% increase (18.5 min) in cycling time to exhaustion [123]. However, it should be noted that it is unclear how time to exhaustion relates to real-life endurance performance, which is usually not until exhaustion but until a finish line is reached.…”
Section: Resultsmentioning
confidence: 74%
“…Although the statistical comparison was made between baseline measurement and post-treatment, and not additionally to the placebo measurements, it seems likely that this is a true effect as there was no change in the placebo treatment. Another study confirmed these findings in untrained females treated with 50 mg prednisone daily for 1 week, which showed a 39% increase (18.5 min) in cycling time to exhaustion [123]. However, it should be noted that it is unclear how time to exhaustion relates to real-life endurance performance, which is usually not until exhaustion but until a finish line is reached.…”
Section: Resultsmentioning
confidence: 74%
“…In conclusion, the mechanisms by which short‐term administration of glucocorticoids are able to improve exercise performance is not completely understood [52,56,58,64]. However, single, acute doses do not appear to have the same performance‐enhancing effect as systematic short‐term administration, despite having similar alterations in blood hormonal and metabolic parameters.…”
Section: Resultsmentioning
confidence: 94%
“…As a consequence glucocorticoids have the potential to be used as ergogenic aids [51]. Table 3 [52‐60] summaries the current available evidence of the effect of glucocorticoids on exercise performance. In 2 separate studies, Arlettaz et al [52] and Le Panse et al [58] investigated the effects of 7 days of prednisolone administration (oral dose 60 mg/d and 50 mg/d, respectively) on exercise performance during submaximal exercise (time to exhaustion at 70%‐75% VO 2max ).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies will be necessary to explore and accurately quantify the mechanisms of proteolysis and glyconeogenesis induced by short-term glucocorticoid intake during this type of exercise. nately, free fatty acids (FFAs) and BCAA were not measured either in this study or in the others performed during more intense submaximal exercise after short-term glucocorticoid intake [5,6] . The purpose of the present study was therefore to characterize the eff ects of short-term (1 week), therapeutic glucocorticoid administration (i. e., prednisone, 50 mg / day orally) on plasma amino acids, FFAs, blood glucose, and several hormones in healthy volunteers performing long-lasting exercise.…”
Section: Introduction ▼mentioning
confidence: 79%